Big Data System for Health Care Records - Nguyen, Tung; Phan, Tan; Vu Khanh, Hoan; Tran Viet, Trung; Nguyen Huu, Duc (VNU Journal of Science: Policy and Management Studies; Vol 33 No 2, 2017)
So far, medical data have been used to serve the need of people’s healthcare. In some countries, in recent years, a lot of hospitals have altered the conventional paper medical records into electronic health records. The data in these records grow continuously in real time, which generates a large number of medical data available for physicians, researchers, and patients in need. Systems of electronic health records share a common feature that they are all constituted from  open sources for Big Data with distributed structure in order to collect, store, exploit, and use medical data to track down, prevent, treat human’s diseases, and even forecast dangerous epidemics.